Introduction agricultural accounting - Wheeling, Barbara M. (Thomson Delmar Learning, 2008)
Introduction to Agricultural Accounting offers an approach for compiling and analyzing accounting information specific to agricultural operations. Unlike typical accounting books, this text addresses the issues and situations unique to the agricultural industry and offers relevant examples of accounting applied to those agricultural operations. The accounting procedures offered build on current practices in agriculture